The Impact of Transposition Skills on Inhibitory Control Performance - Chang-Arana, Álvaro M. (2018)
This study tests whether existing transposition skills have an impact upon inhibitory control. Differences in the degree of transposition practice could translate in different cognitive functionality of musicians and reveal further unexplored evidence of inhibitory control’s plasticity. A total of 64 participants were divided into a group of musicians (n = 34) and a group of non-musicians (n = 30). A transposition task, a music Stroop task and a classic Stroop task were designed. Musicians played their main instruments to play-as-written or transposed conditions from which transposition levels were calculated. All participants responded to the music and the classic Stroop task. The former required participants to choose the note written name while ignoring its location on the staff. Notation system, note-naming system and familiarity with a specific clef was ensured for every music participant. The latter consisted on a motor adaptation of the classic Stroop task where the written word had to be ignored and instead of that pick the perceived colour. Accuracy, reaction time and a composite score was calculated for both tasks. Stroop tasks succeeded in eliciting an inhibitory control response. However no inhibitory control performance differences according to the transposition skill level were detected.